Peran Semiotika Umberto Eco dalam Jurnalisme Investigasi: Studi Kasus Terbunuhnya Vina dan Eky di Cirebon - Pranawukir, Iswahyu; Darmawan, Zakaria Satrio; Syarah, Maya May; Kusuma, Ema; Setianti, Yanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study examines the application of Umberto Eco's semiotics in investigative journalism, focusing on the news coverage of the Vina and Eky murder case in Cirebon. The research analyzes the news article titled